Comparative transcriptome and metabolome analysis reveals the differential response to salinity stress of two genotypes brewing sorghum - Wei Zhou; Zhen Guo Wang; Yan Li; Guo Jiang Wu; Mo Li; Zhi Lan Deng; Feng Juan Cui; Qing Quan Xu; YiMeng Li; Ya Xing Zhou (Scientific Reports)
Abstract Salinity tolerance in brewing sorghum is a very important trait, especially in areas that are affected by soil salinity. In order to elucidate the mechanism underlying salt tolerance, we conducted a comparative analysis of the transcriptome and metabolome in two distinct sweet sorghum genotypes, namely the salt-tolerant line NY1298 and the salt-sensitive line MY1176, following exposure to salt treatment. Our initial findings indicate the presence of genotype-specific responses in brewing sorghum under salt stress conditions. Notably, there were variations in the expression of genes and metabolites among different genotypes in response to high-salt stress. Specifically, certain transcription factors belonging to the WRKY, MYB, and NAC families were identified as being involved in the response to increased external salinity. WGCNA analysis identified stage-specific gene expression for different salinity gradients in each cultivar, and explored the gene function by KEGG enrichment analysis. Combined analysis of DEGs and DEMs in hormone synthesis found AUX/IAA, SAUR, CRE1, A-ARR, PP2C, SNRK2 genes, and 3-indoleacetic acid and jasmonic acid were evidently differential expression among different salt concentrations. Taken together, our study carried out a comprehensive overview of two genotypes of brewing sorghum gene and metabolite expression differences in response to salt stress, and expanded the understanding of responsive mechanism of brewing sorghum to salt stress.